2016
DOI: 10.18632/oncotarget.9049
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and intratumoral balances between monocytes/macrophages and lymphocytes predict prognosis in hepatocellular carcinoma patients after surgery

Abstract: The peripheral neutrophil-monocyte/lymphocyte ratio (NMLR) and intratumoral CD16/CD8 ratio (iMLR) may have prognostic value in hepatocellular carcinoma (HCC) patients after curative resection. In this study, the circulating NMLR was examined 387 HCC patients who underwent curative resection between 2006 and 2009. Intratumoral levels of CD4, CD8, CD16 and CD68 and the CD16/CD8 ratio were determined immunohistologically. The prognostic values of clinicopathological parameters, including NMLR and iMLR, were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 45 publications
1
39
1
Order By: Relevance
“…Cancer can stimulate platelet activity; conversely, platelets can interact with tumor cells and produce several growth factors that facilitate cancer growth, migration, epithelial–mesenchymal transition, and metastasis . Our recent studies also supported the predictive roles of systemic immune cells (peripheral neutrophil, monocyte, and lymphocyte ratio, neutrophil‐to‐lymphocyte ratio (NLR), monocyte‐to‐lymphocyte ratio (MLR), and neutrophil, monocyte, and lymphocyte ratio (NMLR)) in HCC . Similarly, a number of studies have shown that preoperative peripheral immune cell counts or ratios such as monocyte counts , platelet–lymphocyte ratio (PLR) , and platelet–neutrophil–lymphocyte ratio (PNLR) were potential risk factors for dropout before and for recurrence of patients with HCC after liver resection.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Cancer can stimulate platelet activity; conversely, platelets can interact with tumor cells and produce several growth factors that facilitate cancer growth, migration, epithelial–mesenchymal transition, and metastasis . Our recent studies also supported the predictive roles of systemic immune cells (peripheral neutrophil, monocyte, and lymphocyte ratio, neutrophil‐to‐lymphocyte ratio (NLR), monocyte‐to‐lymphocyte ratio (MLR), and neutrophil, monocyte, and lymphocyte ratio (NMLR)) in HCC . Similarly, a number of studies have shown that preoperative peripheral immune cell counts or ratios such as monocyte counts , platelet–lymphocyte ratio (PLR) , and platelet–neutrophil–lymphocyte ratio (PNLR) were potential risk factors for dropout before and for recurrence of patients with HCC after liver resection.…”
Section: Introductionsupporting
confidence: 77%
“…Although the predictive ability of NMLR was reported previously , here, it was not solely the analysis period change in previous study. For the first time, we developed two specific OS and RFS nomograms for resected HCC prognosis incorporating systemic immune cell counts or ratios based on a comprehensive comparison analysis of their prognostic abilities that could reflect the balance of host inflammatory and immune status.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Subsequently, 3 articles did not meet the inclusion criteria and were therefore excluded. Eventually, seven studies, comprising a total of 2,507 patients, were considered eligible for the present meta-analysis18242526272829. The PRISMA flow diagram of the study selection process was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we compared the relationship between FIB-4 and other inflammation-associated parameters including the Forns index, APRI, Glasgow prognostic score (GPS), prognostic index (PI), and prognostic nutritional index (PNI) [28]. Our results indicated that the FIB-4 score was positively correlated with the Forns index and APRI in both sets (Table S2).…”
Section: Resultsmentioning
confidence: 99%